Periodontal Cosmetic Surgery - Concept of Gingival Depigmentation (Bangladesh Journal of Dental Research & Education, 2015)
A smile is more than a method of communication and is a means of socialization and attraction. The harmony of the smile is determined not only by the shape, the position and the color of the teeth but also by the gingival tissues. Gingival pigmentation is well documented in the literature and is considered to be multifactorial. This problem aggravates in patients with gummy smile. There are various treatment modalities for managing this quality of life hampering, esthetic problem including chemical, surgical, cryotherapy, radiotherapy, not the least LASER. The most important factor for determining the treatment for gingival melanin pigmentation is the type of pigmentation, patient acceptance of treatment procedure, its prevalence and its esthetic importance depending on the skin complexion of the patient. DOI: http://dx.doi.org/10.3329/bjdre.v5i1.22455 Bangladesh Journal of Dental Research and Education Vol.5(1) 2015: 19-21